Co-occurrence of IgE and IgG autoantibodies in patients with chronic spontaneous urticaria. (17th March 2020) - Asero, R; Marzano, A V; Ferrucci, S; Lorini, M; Carbonelli, V; Cugno, M
Summary: Chronic spontaneous urticaria (CSU) pathogenesis shows a complex and still unclear interplay between immunoglobulin (Ig)G- and IgE-mediated autoimmunity, leading to mast cell and basophil degranulation and wheal formation. The objective of this study was to evaluate at the same time IgE- and IgG-reactivity to well recognized and recently reported autoantigens in CSU patients, and to assess the effects of such reactivity on response to the anti-IgE monoclonal antibody omalizumab. Twenty CSU patients underwent omalizumab treatment. Urticaria activity score 7 (UAS7) was recorded at baseline and at different drug administration time-points for categorizing early-, late- or non-responders. At baseline, sera from the 20 patients and from 20 controls were tested for IgE and IgG autoantibodies to high- and low-affinity IgE receptors (FcεRI and FcεRII), tissue factor (TF) and thyroglobulin (TG) by immunoenzymatic methods. Antibody levels were compared with those of controls and analysed according to response. Eighteen patients were omalizumab responders (11 early and seven late), while two were non-responders. More than 50% of patients had contemporary IgE and IgG to at least to one of the four different autoantigens. Late responders showed higher levels of both anti-TF IgE and IgG than early responders ( P = 0·011 and P = 0·035, respectively). Twenty-five per cent of patients had levels of anti-FcεRI IgE, exceeding the upper normal limit, suggesting that it could be a novel auto-allergen in CSU. In CSU, there is an autoimmune milieu characterized by the co-existence of IgE and IgG autoantibodies to the same antigen/allergen, particularly in late responders to omalizumab, possibly explaining the slower response. Graphical Abstract: Chronic spontaneous urticaria (CSU) has a complex and still unclear pathogenesis mainly involving autoimmunity and/or autoallergy, eventually leading to mast cell/basophil degranulation and wheal formation. The humanized monoclonal anti-IgE antibody omalizumab is very effective in the treatment of CSU resistant to antihistamines; however, several patients show a late response to this drug. In CSU patients, our study demonstrates the coexistence of IgE- and IgG-mediated autoimmunity to the same autoantigens, particularly in late omalizumab responders, explaining the slower clinical response to the drug when the high affinity IgE receptor (FcεRI) is involved.